Exploring the Uses and Gratifications of Agricultural Blog Readers - Courtney Meyers; Kate Gracey; Erica Irlbeck; Cindy Akers (Journal of Applied Communications, 2015)
Blogs are a type of social media that present a unique opportunity to provide information to a large audience without the constraints of traditional media’s gatekeeping barriers. Within agriculture, several studies have examined agricultural blogs but not from the perspective of blog readers. Therefore, the purpose of this study was to describe the uses and gratifications of agricultural blog readers. This study used a descriptive survey research design and online questionnaire to assess agricultural blog readers’ demographics, Internet and blog use, attitudes toward agriculture, and motivations for reading blogs. Findings indicated most respondents had direct experience in agriculture and were supportive of the industry. The strongest motivations for accessing agricultural blogs were to find out what other people think about important issues or events and to find alternatives not covered by traditional news sources. Blogs proved to be a useful source of information, but more should be done to expand reach beyond those in the industry. Additional research is needed to more fully describe agricultural blog readers’ uses and gratifications.
Keywords: Blogs; uses and gratifications; social media; agricultural communications; Association for Communication Excellence Conference